Simulação numérica da evaporação de líquidos em meios porosos expostos à atmosfera através de modelo de escala de poros - Goulart, Elisa Valentin (2007)
The mathematical modeling of the evaporation of liquid from porous surfaces are extremely important in a great number of practical applications, varying since industrial applications, as processes of superficial treatment, to the applications in ambient problems, as the use of hazard liquid and studies of ambient impact of launching harmful liquids in the atmosphere. The pore network models appear with important tool for the calculation of the taxes of evaporation of liquids. This work aims at to implement a pore network model capable predict the drying rates of the liquids and the phase distributions of liquids and vapor. And analyzing the influence of the governing parameters in the evaporation process. The model was able to predict with reasonable agreement the results of Yiotis et al. (2001). The results show that under more intensive flow the influence of the porous medium is more evident, limiting the evaporation process, then when under less intensive flow